2012
DOI: 10.1007/s00253-012-4618-7
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of ethylene glycol in Escherichia coli

Abstract: Ethylene glycol (EG) is an important platform chemical with steadily expanding global demand. Its commercial production is currently limited to fossil resources; no biosynthesis route has been delineated. Herein, a biosynthesis route for EG production from D-xylose is reported. This route consists of four steps: D-xylose → D-xylonate → 2-dehydro-3-deoxy-D-pentonate → glycoaldehyde → EG. Respective enzymes, D-xylose dehydrogenase, D-xylonate dehydratase, 2-dehydro-3-deoxy-D-pentonate aldolase, and glycoaldehyde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 22 publications
0
90
4
1
Order By: Relevance
“…EG should not exhibit toxicity to E. coli in low concentrations. It has been shown previously that EG can even be biosynthesized in E. coli [50]; therefore, possible traces of it remaining within the porous particle structure are not likely to solely contribute to overall antibacterial effect The increased toxicity could, therefore, be related to possible additional products of reaction and/or synergistic interplay among the main and trace components. This inconsistency in antibacterial activity could also be explained by unforeseen aggregation of the nanoparticles during bioassay.…”
Section: Antibacterial Activitymentioning
confidence: 97%
“…EG should not exhibit toxicity to E. coli in low concentrations. It has been shown previously that EG can even be biosynthesized in E. coli [50]; therefore, possible traces of it remaining within the porous particle structure are not likely to solely contribute to overall antibacterial effect The increased toxicity could, therefore, be related to possible additional products of reaction and/or synergistic interplay among the main and trace components. This inconsistency in antibacterial activity could also be explained by unforeseen aggregation of the nanoparticles during bioassay.…”
Section: Antibacterial Activitymentioning
confidence: 97%
“…Previous studies have shown that deletion of these three genes disables the strain's capability to grow on D-xylose or D-xylonic acid but does not interfere with cellular growth on LB or glucose (Liu et al, 2012;Liu et al, 2013). These results indicated that the strain's central metabolism was not influenced by the ϭϭ blockage of D-xylose metabolism, suggesting that the BD pathway can be introduced to the chassis.…”
Section: Construction and Optimization Of The Enzymatic Reactor Modulementioning
confidence: 55%
“…Furthermore, the industrial process also suffers from low selectivity of MEG because higher order glycols are also produced in the process due to the increased reactivity of Ethylene oxide towards MEG than to water (Forkner et al, 2000;Rebsdat and Mayer, 2000). It is thus of interest to explore the routes for biological production of MEG from renewable feedstocks such as sugars using engineered microbial organisms, and this interest has obtained significant attention from the scientific community recently (Alkim et al, 2015;Liu et al, 2013;Pereira et al, 2016a;Pereira et al, 2016b;Stephanopoulos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%